Effects of Legislation Overlapping Regarding Transnational Crime - Prasetio, Imam; Naibaho, Nathalina; Yudhy, Dhianti Afifah Nabila (Magister of Law, Faculty of Law, University of Mataram, 2023)
Globalization has a dominant role in the trade of goods/services, people, technologies, and information. The globalization targets are cultural, economic, and political globalization. Unintentionally, problems arise in society, such as transnational rights issues (transnational crime) caused by globalization. The most common transnational crime is sexual exploitation, which occurs in both men and women. Therefore, regarding the handling of TIP in Indonesia, complementary and correlated regulations or legislation are needed to eradicate TIP. Considering that currently, there are regulations that overlap with each other. As happened in the criminal act of trafficking in persons and the law on the protection of Indonesian migrant workers, the two laws should synergize to prevent, handle, and eradicate TIP. Thus, law enforcers can also be maximal in carrying out their duties, especially in taking action against TIP perpetrators.